Políticas públicas y gestión educativa, entre la formulación y la implementación de las políticas educativas. (2020)
This review article is the result of research on public policy, educational management and teacher training in Colombia. For its development, some concepts in which education policy is framed and the relevance that it has in the educational processes carried out in the country are described. Likewise, the concepts that have been established from different perspectives for public policy, educational management, teacher training, the relationship that these concepts have with the being and the duty to be, and the challenges of teacher training in relation to the approaches of educational policies are presented. From this, it can be concluded that education policies must be created on the principle of transversality, from which they take each of the important elements to provide a quality education that directly contributes to the development and resolution of social problems.